The Role of ChatGPT in Knowledge Management: Its Impact on Innovation and Performance of Micro, Small, and Medium Enterprises (MSMEs) - Bakri; Prameswari, Narulita Helen Rahayu; Habibah, Nabila Machsunatul; Chorer, Mohammad Mudhofar; Mun'im, Muhammad Agim Syahrul (PT. LITERASI SAINS NUSANTARA, 2024)
In today's era of globalization and digitalization, knowledge management has become a crucial component for the success of organizations, including MSMEs. This research aims to review existing literature to understand how ChatGPT can be utilized in knowledge management for MSMEs and its impact on innovation and performance. This study is a literature review with a qualitative approach. Data were collected from Google Scholar, one of the leading academic databases, with a literature search conducted for the period 2007-2024 to ensure relevance and currency of the information obtained. The results of the study indicate that ChatGPT has significant potential in enhancing knowledge management, innovation, and performance of micro, small, and medium enterprises (MSMEs). This technology offers various benefits, including quick access to information, strategic recommendations, and support for innovation. The use of ChatGPT helps MSMEs manage knowledge more efficiently, improve customer service quality, and optimize business operations.